Hearing restoration with cochlear implants after translabyrinthine vestibular schwannoma resection - Bohr, Christopher; Müller, Susanna; Hornung, Joachim; Hoppe, Ulrich; Iro, Heinrich (HNO, 2017)
BACKGROUND: Hearing restoration after translabyrinthine vestibular schwannoma resection is a challenge. Because the cochlea can begin to ossify a few months after cochlear or labyrinthine injury, the time interval for cochlear implant surgery is limited. To avoid complete ossification and to prolong the time interval until cochlear implantation, it is possible to insert a placeholder (depth gauge) into the cochlea and perform the cochlear implant surgery at a later time point (two-stage approach). OBJECTIVE: The aim of this retrospective case series was to present the outcomes after restoration of hearing with cochlea implants in six patients and to evaluate the use of the depth gauge in practice. METHODS: The hearing outcome of all patients with (n = 3) and without (n = 3) insertion of a depth gauge was measured with the Freiburg monosyllabic test without background noise at 65 dB. The first measurement was performed prior to the translabyrinthine vestibular schwannoma resection, the last measurement was performed up to 48 months after cochlear implantation. RESULTS: All 6 patients reached 22.5 ± 36.57% prior to vestibular schwannoma resection and 41.3 ± 26% 12 months after cochlear implantation. The understanding values of the patients with a depth gauge were 25.8 ± 16% after 12 months which is below the values of the other patients with 56.6 ± 25.0%. No severe intraoperative or postoperative complications occurred in any patient. CONCLUSION: The two-stage approach for cochlear implantation with depth gauge insertion following labrynthine incision and intact nerve appears to represent a very promising and safe variation for hearing restoration. Intensified research on this approach seems to be justified and necessary.
EVALuna2:33160